2021
DOI: 10.1021/acs.langmuir.1c00954
|View full text |Cite
|
Sign up to set email alerts
|

A Silica Coating Approach to Enhance Bioconjugation on Metal-Encoded Polystyrene Microbeads for Bead-Based Assays in Mass Cytometry

Abstract: Bead-based assays in flow cytometry are multiplexed analytical techniques that allow rapid and simultaneous detection and quantification of a large number of analytes from small volumes of samples. The development of corresponding bead-based assays in mass cytometry (MC) is highly desirable since it could increase the number of analytes detected in a single assay. The microbeads for these assays have to be labeled with metal isotopes for MC detection. One must also be able to functionalize the bead surface wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…122 There exists an ample variety of materials modified with this procedure: silica-coated Eu-encoded polystyrene beads, polystyrene core/SiO 2 shell particles, SiO 2 -coated Fe 3 O 4 particles and SiO 2 NPs doped with Ru(bpy) 3 Cl 2 , among others. [123][124][125][126][127][128][129][130][131][132][133][134][135][136] Alternatively, it is possible to synthesize anhydrides from polycarboxylic acids such as EDTA as shown in Scheme 15. 137 Finally, Amesh et al reported the synthesis of a COOH silane precursor from the reaction between APTES and succinic anhydride in chloroform and using an anhydrous CaCl 2 moisture trap tube.…”
Section: Click Thiol-ene Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…122 There exists an ample variety of materials modified with this procedure: silica-coated Eu-encoded polystyrene beads, polystyrene core/SiO 2 shell particles, SiO 2 -coated Fe 3 O 4 particles and SiO 2 NPs doped with Ru(bpy) 3 Cl 2 , among others. [123][124][125][126][127][128][129][130][131][132][133][134][135][136] Alternatively, it is possible to synthesize anhydrides from polycarboxylic acids such as EDTA as shown in Scheme 15. 137 Finally, Amesh et al reported the synthesis of a COOH silane precursor from the reaction between APTES and succinic anhydride in chloroform and using an anhydrous CaCl 2 moisture trap tube.…”
Section: Click Thiol-ene Reactionsmentioning
confidence: 99%
“…There exists an ample variety of materials modified with this procedure: silica-coated Eu-encoded polystyrene beads, polystyrene core/SiO 2 shell particles, SiO 2 -coated Fe 3 O 4 particles and SiO 2 NPs doped with Ru(bpy) 3 Cl 2 , among others. 123–136…”
Section: Anchoring Cooh Groups To Silica-based Materialsmentioning
confidence: 99%
“…[ 10–14 ] A very promising material combination for single particle‐based assays is achieved by merging the benefits of polystyrene (PS) and silica (SiO 2 ) particles in a core–shell particle format. [ 12,15,16 ]…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] A very promising material combination for single particle-based assays is achieved by merging the benefits of polystyrene (PS) and silica (SiO 2 ) particles in a core-shell particle format. [12,15,16] Besides equipping CS particles with optical or electrochemical features and grafting (bio)chemical units to their outer surface that drive many of the developments in the field, two less explicit aspects gained increasing attention recently, surface morphology and its impact on functional performance [10,17,18] as well as magnetic properties, strongly facilitating handling and processibility [19,20] especially in view of automated workflows. [21,22] Examples of CS particles with magnetic features and controlled surface morphology, however, are scarce.…”
mentioning
confidence: 99%
“…Monodisperse polymeric microspheres with various funcional groups on the surface have attracted widespread attention for a variety of applications such as molecular imprinting technology, charomatography, calibration standards, templates for organic/inorganic composites, and bead-based biomedical assays. Polymeric microspheres with a micrometer-dimension can be prepared by seeded emulsion polymerization, activated swelling suspension polymerization, or dispersion polymerization . In particular, dispersion polymerization is an attractive one-pot method that can prepare monodisperse polymeric microspheres with diameters in the range of 0.5–15 μm …”
mentioning
confidence: 99%